O Gênero Cyathus haller: pers. (Agaricales, Basidiomycota) em áreas de caatinga do Nordeste brasileiro - Cruz, Rhudson Henrique Santos Ferreira da (2013)
Fungi of the family Nidulariaceae or bird s nest fungi present a vase-shaped basidiomata with the wall surface smooth or striated lengthwise and internal structures resembling small bird eggs in a nest, the peridioles. Among the five genera that comprise the group, the more representative is Cyathus Haller: Pers. The Brazilian Northeast region shows major importance for the world s diversity by containing a Brazilian unique and exclusively phytoecological domain, the Caatinga, which lacks particular attention regarding macrofungi. Although the gradual growth of knowledge in recent years, studies are still insipient in the Caatinga domain. Between their various vegetal formations are the Brejos de Altitude , described as islands with moist perennial vegetation, low soil fertility and annual precipitation of 900 1.300 mm. This study aimed to evaluate the taxonomic richness of Nidulariaceae fungi in Caatinga s areas of Northeastern Brazil, describing and identifying species, as well as expanding the collection of Herbarium UFRN Fungos. For description of Nidulariaceae fungi was followed the proposed by specialized literature in the group. We have found and described 10 species of the genus Cyathus, namely: C. earlei Lloyd, C. gayanus Tul. & C. Tul., C. gracilis H.J. Brodie, C. intermedius (Mont.) Tul. & C. Tul., C. limbatus Tul. & C. Tul., C. montagnei Tul. & C. Tul., C. pallidus Berk. & M.A. Curtis, C. poeppigii Tul. & C. Tul., C. striatus (Huds.) Willd. and C. tríplex Lloyd. Beyond these have been described four new species to science: Cyathus calvescens R. Cruz & Baseia sp. nov., C. hortum R. Cruz & Baseia sp. nov., C. magnomuralis R. Cruz & Baseia sp. nov. and C. parvocinereus R. Cruz & Baseia sp. nov. Two samples were identified only to genus level. No member of Mycocalia J.T. Palmer, Nidula V.S. White, Nidularia Fr. and Crucibulum Tul. & C. Tul. has been found, however the results were extremely valuable for being an unprecedented work in Caatinga, and importante tool for implementation of conservation projects and sustainable utilization of this domain